2018
DOI: 10.1002/poi3.173
|View full text |Cite
|
Sign up to set email alerts
|

How Does Social Capital Associate With Being a Victim of Online Hate? Survey Evidence From the United States, the United Kingdom, Germany, and Finland

Abstract: Although online hate has become a phenomenon in online interaction, we do not know how the quality of online social relations is linked to the risk of being a target of hostile behavior online. In this article, we examine how cognitive social capital online (i.e., trust and sense of belonging) is associated with the risk of being a victim of online hate by utilizing cross‐national data collected in 2013–14 among American (n = 1,033), British (n = 999), German (n = 978), and Finnish (n = 555) adolescents and yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 86 publications
(161 reference statements)
1
7
0
Order By: Relevance
“…Cypriot, Korean, and Spanish adolescents showed lower odds of being perpetrators of online hate, and Thai and American adolescents had higher odds compared to German adolescents. Understanding national differences in the frequency rates of online hate is complex and most likely influenced by individual and wider societal factors (e.g., the presence of antihate speech laws, terrorist attacks) [18,39,40]. Age was positively associated with being a bystander to and perpetrator of online hate, indicating that adolescents become, with increasing age, more likely to witness online hate and also post or forward hateful or denigrating material online.…”
Section: Discussionmentioning
confidence: 99%
“…Cypriot, Korean, and Spanish adolescents showed lower odds of being perpetrators of online hate, and Thai and American adolescents had higher odds compared to German adolescents. Understanding national differences in the frequency rates of online hate is complex and most likely influenced by individual and wider societal factors (e.g., the presence of antihate speech laws, terrorist attacks) [18,39,40]. Age was positively associated with being a bystander to and perpetrator of online hate, indicating that adolescents become, with increasing age, more likely to witness online hate and also post or forward hateful or denigrating material online.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, trust could be a risk factor: People who are more trusting of others may be more prone to believe in the content of hateful comments. More so, high trust and a sense of belonging increase the risk of becoming a victim of online hate speech (Kaakinen, Keipi, Oksanen, & Räsänen, 2018). Nevertheless, basic societal qualities-such as social capital, mutual trust, and cooperativeness-should be taken into account when thinking about human resilience to hate speech.…”
Section: Discussionmentioning
confidence: 99%
“…While the preceding mechanisms have a common root, opposition sparking hostility, there is another intriguing explanation for the statistical association. Perpetrators (and victims; Kaakinen, Keipi, Oksanen, & Räsänen, 2018) of online hate tend to have certain dispositions (Kurek, Jose, & Stuart, 2019; McCreery & Krach, 2018), which can be clustered across geographical areas (for psychological traits of US regions, see Rentfrow et al, 2013). It is reasonable to assume that a region's dispositional hostility can foster polarization and cross‐group rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Online hostility can emerge from current local events (Williams & Burnap, 2015) or local history (Payne, Vuletich, & Brown–Iannuzzi, 2019). For example, Kaakinen, Oksanen, and Räsänen (2018) observed that the Paris terror attack from November 2015 was associated with a rise in fear and intergroup hostility among Finnish internet users, who related to the pre–attack situation of their fellow Europeans (c.f., Oksanen et al, 2018). According to the authors, this finding is in line with the general observation that threatening societal events serve as a trigger for outgroup blaming and intergroup hostilities.…”
Section: Regional Attitudes Towards Minorities and Online Hostilitymentioning
confidence: 99%